POTENSI AIR HUJAN UNTUK KETERSEDIAAN AIR BERSIH DI DAERAH GEOTHERMAL (STUDI KASUS DESA PENTADIO BARAT) - Putri, Putri Syaferina Djafar; Husnan, Rawiyah; Labdul, Barry Yusuf (Composite Journal, 2024)
Water is essential for human life, and its scarcity can significantly impact communities. In West Pentadio village, located on the lakeshore, residents struggle with obtaining clean water due to the murky, sulfurous geothermal water. To address this, a study was conducted to evaluate rainwater harvesting as a solution. Analyzing data from DAS Bionga over 13 years, the study used Normal, Log Normal, Log Pearson III, and Gumbel distributions for rainwater distribution and the Mononobe method for rainfall intensity. Population projections from 2021 to 2026, ranging from 1,026 to 1,118 people, indicate increasing daily clean water needs from 71,820 liters to 78,260 liters. The analysis revealed Cv = 0.32, Cs = 1.98, and Ck = 0.32, with Log Pearson III as the most appropriate distribution. The potential rainwater volume is 2,611,497.52 liters per hour with an intensity of 166.268 mm/hour. Conservation rates are 16.5% for one family and 15.2% for 4-5 families. Budgeting using 2020 prices in Gorontalo Regency, a container for one family (1.2 x 1.2 x 1.2 meters) costs Rp. 3,044,703, while a larger container for 4-5 families (2 x 2 x 2 meters) costs Rp. 7,944,877. This rainwater harvesting system offers a viable solution to improve access to clean water for the village.